Positive Response of Indian Judiciary to Electronic Evidences: Understanding the Role of Digital Evidence in the Indian Judicial System (Journal of Advances and Scholarly Researches in Allied Education, 2021)
The innovation of computers and digitalization is one of the greatest achievements of mankind. In the age of the digitalized world, governments of many countries have adopted digitalization in their administration. Few years back, the Indian government has started the ‘Digital India’ campaign to promote the use of digitalization in our day to day life too, which would certainly help to speed up the development of our country. The enormous growth of digitalization in governance, commerce, and private well as business activities has made it the fundamental pillar of documentation, processing and communication. The evidentiary value of an electronic record totally depends upon its quality. The Indian Evidence Act, 1872 has widely dealt with the evidentiary value of the electronic records. E-mail is recognized as a valid and authentic source of evidence. Generally, e-mails are submitted through print outs attached with the Certification of us 65B of the Indian Evidence Act, 1872.Nowadays, Mobile phones are very useful electronic device and very resourceful. The Researcher in through this Article wants to aware all about the laws dealing with electronic evidences and what type of electronic evidences are admissible and recognized by the law as well as accepted by the Judicial persons too.